The relationship between organizational culture and innovation through Vietnamese employee’s perspective - Nham, Phong Tuan; Pham, Thi Trang (Journal of International Economics and Management, 2015)
In a globalized business setting, a national culture that impacts strongly innovation is of utmost importance especially in developing countries that expect to improve income levels and compete globally. Since organizational culture is embedded in national culture, studying culture at the organizational level is apt especially when organizational culture and innovation have been found to increase performance. This study examines relationship between organizational culture and innovation through Vietnamese employees’ perspective. More specifically, cultural traits of Empowerment, Team Orientation, Capability Development, Creating Change, Customer Focus and Organizational Learning on Innovation are considered in this paper. The respondents include 130 Vietnamese employees in both the private and public sectors. The results showed that Organizational learning, capability development, team orientation, creating change were found to be significant contributors to Innovation new to the organization and Innovation new to the industry. Implications and future recommendations are also discussed in this paper.